Accounting for British Muslim's educational attainment: gender differences and the impact of expectations. Issue 2 (17th February 2018) - Khattab, Nabil; Modood, Tariq
Abstract: This study compares the educational attainment of Muslim and Christian White-British boys and girls at the following junctions: Key Stage 2, Key Stage 3, GCSE, getting into universities and achieving a place at a Russell Group university. The study utilises the Longitudinal Study of Young People in England waves 1–6 with linked data from the National Pupil Database. The analysis shows that once we take previous school performance into account, Muslim students seem to be performing as well as the majority group, even in attending Russell group universities. Muslim girls seem to now be outperforming Muslim boys, especially in relation to their school performance. Furthermore, parental expectations and students' own expectations play an important role in determining the attainment of students. The study concludes that the higher achievement of young Muslims may be strongly correlated with their own unusually high expectations of going to university; but a primary source of the latter is likely to be the parents' unusually high expectations, the messages they receive and the discipline in place in relation to schoolwork at home and their relationship with their parents and their parents' norms.